Evaluating the survival strategies adopted by single mothers to enhance their livelihood in Zimbabwe - Kang’ethe, S.M.; Mafa, Itai (2020)
Poverty and its eradication are presently at the pinnacle of all global development policies inexorably attracting the attention of numerous prominent organizations including the World Bank and the United Nations. However and irrefutably, feminization of poverty especially among the single mothers is a huge stumbling block to making a significant score to the Millennium Development Goal (MDGs) number three, which is concerned with women empowerment. The aim of this article is, through a review of literature methodology, to explore the survival strategies adopted by single mothers. Findings indicate the following factors underpinning the prevalence of single mothers in Zimbabwe: divorce and separation; death from diseases such as HIV/AIDS; out-of-wedlock births; and choice of being single mothers. Single mothers were also found to enjoy support from the following sources: international/donor organization, government, family and communities; and from faith based organizations. Ultimately, the paper reveals the following survival strategies: prostitution, entrepreneurship and engagement in women group organizations. As the way forward, the paper recommends the following: re-implementing balanced and favourable women friendly policies; erecting educational and sustainable projects friendly to women; and fostering partnership between the government and the NGOs dealing with women development and advancement.